Method for preparing iron phosphate for battery and application of iron phosphate

By preparing iron phosphate for batteries, iron phosphate dust collecting materials with high moisture content and incomplete transformation are processed, and its recycling and recycling are realized, the sand abrasive performance of iron phosphate and the uniformity of product are improved, and the problems of high moisture content and incomplete transformation in the preparation process of iron phosphate in the prior art are solved.

CN119612467AActive Publication Date: 2025-03-14GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411849790.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-14
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

In the prior art, there are problems of high moisture content and incomplete transformation of iron phosphate during the preparation process, resulting in unstable Li/P ratio of lithium iron phosphate, affecting battery capacity and cycling performance. At the same time, the uneven size of iron phosphate particles leads to poor sanding performance, which is prone to risk of blockage.

Method used

A method for preparing iron phosphate for batteries is adopted, including preparing a mixture of iron phosphate dust collecting material and aqueous phosphoric acid solution, obtaining a liquid phase through leaching treatment and solid-liquid separation, and reacting with elemental iron, then mixing with surface dispersant, performing a segmented oxidation and aging treatment, and finally baking to obtain iron phosphate.

Benefits of technology

This method can effectively treat iron phosphate dust collecting materials with high moisture content and incomplete transformation, realize their recycling and recycling, and reduce production costs. By controlling the reaction conditions and adding surface dispersant, the sanding performance of iron phosphate and the uniformity of product are improved, spontaneous precipitation and the formation of bulk products are avoided, and the obtained iron phosphate has excellent battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a method for preparing iron phosphate for a battery and application of the iron phosphate, and relates to the technical field of resource recovery and preparation. The method for preparing the iron phosphate for the battery can be used for treating the anhydrous iron phosphate dust collection material which is high in water content and incomplete in crystal transformation, the iron phosphate in the iron phosphate dust collection material is leached out through a phosphoric acid aqueous solution, after Fe < 3 + > is reduced into Fe < 2 + >, porous iron phosphate is synthesized in combination with a surface dispersing agent and segmented oxidation aging treatment, and the iron phosphate for the battery is obtained through roasting. The circulation of the dust collecting material and the recycling of the iron phosphate are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of resource recovery, and in particular to a method for preparing iron phosphate for battery and application thereof. Background Art

[0002] With the rapid expansion of the new energy industry, the demand for battery materials has increased year by year. Lithium iron phosphate cathode material is one of the important cathode materials due to its abundant raw material sources, low price, high capacity, good safety, etc. As an important precursor material of lithium iron phosphate, iron phosphate has physical and chemical properties such as chemical composition, structure, morphology, particle size, etc. that largely determine the comprehensive performance of lithium iron phosphate cathode materials.

[0003] At present, the preparation process of iron phosphate in industry usually adopts wet synthesis to obtain dihydrated iron phosphate. Then, in production, dihydrated iron phosphate is converted into anhydrous iron phosphate through sintering, and H2O in dihydrated iron phosphate is removed as much as possible. However, during the sintering process, some fine iron phosphate is easily sucked away by the blower and enters the bag dust collector. At this time, the product is not sintered completely. At the same time, it is easy to combine with water molecules in the exhaust gas during this process to obtain iron phosphate with a high water content, which is commonly known as iron phosphate dust collection material in the industry. Its output is about 3%~7% of qualified products. The high water content in iron phosphate will affect the Li / P ratio of lithium iron phosphate in the process of preparing lithium iron phosphate, resulting in reduced battery capacity and cycle performance. Therefore, iron phosphate with high water content and incomplete crystal transformation cannot be used as a normal product. In addition, in the preparation process of lithium iron phosphate, iron phosphate needs to be sand-milled and crushed. Some iron phosphate particles are large and difficult to crush, which can easily lead to the risk of blockage in subsequent spraying.

[0004] Therefore, it is important to provide a method for preparing iron phosphate with better sanding performance by using iron phosphate dust collecting material. Summary of the invention

[0005] The present disclosure aims to solve at least one of the technical problems existing in the prior art. To this end, the present disclosure provides a method for preparing iron phosphate for battery.

[0006] The present disclosure also proposes the application of the above method in the recovery of iron phosphate dust collection material.

[0007] According to the first aspect of the present disclosure, a method for preparing iron phosphate for a battery comprises the following steps: 1) preparing a first mixture of iron phosphate dust collection material and phosphoric acid aqueous solution, leaching treatment, and first solid-liquid separation to obtain a first liquid phase; preparing a second mixture of the first liquid phase and elemental iron, reacting, and second solid-liquid separation to obtain a second liquid phase; The leaching temperature is not higher than 50°C; the molar ratio of phosphorus in the phosphoric acid aqueous solution to the elemental iron is 1:1.05-1.2; 2) preparing a third mixture of the second liquid phase and a surface dispersant, and subjecting the third mixture to a staged oxidation aging treatment; performing a third solid-liquid separation to obtain a solid phase; and calcining the solid phase to obtain the ferric phosphate; The surface dispersant includes at least one of a cationic surfactant, an anionic surfactant, and a nonionic surfactant; the cationic surfactant includes a quaternary ammonium surfactant; the anionic surfactant includes at least one of sodium dodecyl sulfate (SDS) and sodium dodecylbenzene sulfonate (SDBS); the nonionic surfactant includes at least one of a polyether surfactant and a hydroxy surfactant; The number of segments of the segmented oxidation aging treatment is N, and N is a positive integer not less than 2; The calcination temperature is not less than 580° C. and the calcination time is not less than 2 h.

[0008] The method for preparing iron phosphate for battery according to the present disclosure has at least the following beneficial effects: The method for preparing iron phosphate for battery can be used to treat anhydrous iron phosphate dust collection material with high water content and incomplete crystal transformation, realize the circulation of dust collection material and the recycling of iron phosphate, and reduce production costs. The iron phosphate in the iron phosphate dust collection material is dissolved in phosphoric acid aqueous solution at low temperature, avoiding the problem of spontaneous precipitation caused by excessively high leaching temperature, which affects the uniformity of the product, and makes the product BET <3; and the elemental iron is used to consume H + At the same time, Fe 3+ Reduction to Fe 2+ By controlling the amount of elemental iron added, the yield of P is effectively guaranteed, the cost is reduced, and the problem of Fe / P imbalance in iron phosphate is avoided. The selected surface dispersant and segmented oxidation aging treatment are further used to improve the looseness and sand grinding performance of iron phosphate, and porous iron phosphate is synthesized; in the first stage of oxidation aging treatment, the surface dispersant is conducive to avoiding high-temperature spontaneous precipitation to form block products, and the synthesized small amount of iron phosphate as a seed also has the effect of increasing the precipitation rate. Finally, the qualified iron phosphate product for battery is obtained by roasting.

[0009] According to some embodiments of the present disclosure, the iron phosphate dust collecting material is derived from a rotary kiln. In terms of mass percentage, the iron phosphate dust collecting material has a H2O content of 1% to 5%, a Fe content of 33% to 36%, a P content of 18.5% to 20.5%, and an impurity element content of 0 to 100 ppm.

[0010] According to some embodiments of the present disclosure, the material-liquid ratio of the ferric phosphate dust collecting material to the phosphoric acid aqueous solution is 20 g to 200 g: 1 L. For example, it can be 20 g: 1 L, 30 g: 1 L, 40 g: 1 L, 50 g: 1 L, 60 g: 1 L, 70 g: 1 L, 80 g: 1 L, 90 g: 1 L, 100 g: 1 L, 110 g: 1 L, 120 g: 1 L, 130 g: 1 L, 140 g: 1 L, 150 g: 1 L, 160 g: 1 L, 170 g: 1 L, 180 g: 1 L, 190 g: 1 L or 200 g: 1 L.

[0011] According to some embodiments of the present disclosure, the phosphoric acid concentration in the phosphoric acid aqueous solution is 30% to 50%. For example: it can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49% or 50%, where the phosphoric acid concentration refers to the mass percentage concentration of the phosphoric acid aqueous solution occupied by phosphoric acid. If the phosphoric acid concentration is too high, it is easy to cause spontaneous precipitation of Fe and P elements, affecting product uniformity. If the phosphoric acid concentration is too low, it is easy to cause the dissolution rate and dissolution amount of subsequent elemental iron to decrease, affecting production.

[0012] According to some embodiments of the present disclosure, the mass ratio of the iron phosphate dust collecting material to the elemental iron is 0.06 to 0.6:1. If the amount of the iron phosphate dust collecting material is too high, it is easy to cause the BET of the product to be too small. For example, it can be 0.06:1, 0.08:1, 0.1:1, 0.12:1, 0.14:1, 0.16:1, 0.18:1, 0.2:1, 0.22:1, 0.24:1, 0.26:1, 0.28:1, 0.3:1, 0.32:1, 0.34:1, 0.36:1, 0.38:1, 0.4:1, 0.42:1, 0.46:1, 0.48:1, 0.5:1, 0.52:1, 0.54:1, 0.56:1, 0.58 or 0.6:1.

[0013] According to some embodiments of the present disclosure, the elemental iron is derived from at least one of iron sheets and iron powder.

[0014] According to some embodiments of the present disclosure, the leaching temperature is 20°C to 50°C. For example, it may be 25°C, 30°C, 35°C, 40°C, 45°C or 50°C.

[0015] According to some embodiments of the present disclosure, the leaching treatment time is no longer than 4 h.

[0016] According to some embodiments of the present disclosure, the leaching treatment time is 1.5 h to 4 h. For example, it can be 1.5 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h or 4 h.

[0017] According to some embodiments of the present disclosure, the molar ratio of phosphorus in the aqueous phosphoric acid solution to the elemental iron is 1:1.05-1.2. For example, it can be 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09, 1:1.1, 1:1.11, 1:1.12, 1:1.13, 1:1.14, 1:1.15, 1:1.16, 1:1.17, 1:1.18, 1:1.19 or 1:1.2.

[0018] According to some embodiments of the present disclosure, the reaction temperature of the reaction in step 1) is 50°C to 90°C. For example, it may be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C.

[0019] According to some embodiments of the present disclosure, the reaction time of the reaction in step 1) is 6 h to 10 h. For example, it can be 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 or 10 h.

[0020] According to some embodiments of the present disclosure, the concentration of the iron element in the second liquid phase is 110 g / L to 240 g / L. For example, it can be 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L, 160 g / L, 170 g / L, 180 g / L, 190 g / L, 200 g / L, 210 g / L, 220 g / L, 230 g / L or 240 g / L. Thus, it is beneficial to control the viscosity of the reaction solution, facilitate subsequent reactions, avoid subsequent products being too dense, and have a low BET.

[0021] According to some embodiments of the present disclosure, the mass ratio of the iron element in the third mixture to the surface dispersant is 1:0.001-0.005; optionally, the mass ratio of the iron element in the third mixture to the surface dispersant is 1:0.0014-0.0045. For example, it can be 1:0.0014, 1:0.0016, 1:0.0018, 1:0.002, 1:0.0022, 1:0.0024, 1:0.0026, 1:0.0028, 1:0.003, 1:0.0032, 1:0.0034, 1:0.0036, 1:0.0038, 1:0.004, 1:0.0042 or 1:0.0045.

[0022] According to some embodiments of the present disclosure, the quaternary ammonium surfactant contains a hydroxyl group. The quaternary ammonium surfactant includes at least one of SRC-JX-1 and SRC-JX-3.

[0023] According to some embodiments of the present disclosure, the polyether surfactant includes PPEA-15.

[0024] According to some embodiments of the present disclosure, the hydroxyl surfactant includes SRC-JX-2.

[0025] According to some embodiments of the present disclosure, the number of segments of the segmented oxidation aging treatment is 2 to 6. For example, it can be 2, 3, 4, 5 or 6.

[0026] According to some embodiments of the present disclosure, the staged oxidation aging treatment includes one stage oxidation aging treatment to N stage oxidation aging treatment; Each stage of the stepwise oxidation aging treatment includes: adding an oxidant and performing aging treatment. The aging treatment in each stage of the oxidation aging treatment is used to prevent the BET of the product from decreasing and the sanding performance from being reduced.

[0027] According to some embodiments of the present disclosure, the oxidant includes at least one of hydrogen peroxide, oxygen, ozone, and air. If the oxidant is oxygen, ozone, or air, the oxidant can be directly introduced into the third mixture during use.

[0028] According to some embodiments of the present disclosure, the oxidant and Fe 2+ The oxidant is added in an excess of 10% to 20% in the reaction, that is, the total molar amount of the oxidant is equal to the molar amount of Fe in the third mixture. 2+ 110% to 120% of the molar amount required for complete reaction. Thus, the oxidation efficiency can be guaranteed. For example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.

[0029] According to some embodiments of the present disclosure, the mass percentage concentration of the hydrogen peroxide is greater than 27.5%.

[0030] According to some embodiments of the present disclosure, the mass percentage concentration of the hydrogen peroxide is 27.5% to 35%. For example, it can be 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5% or 35%.

[0031] According to some embodiments of the present disclosure, the temperature of the staged oxidation aging treatment is 50°C to 90°C. For example, it can be 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C.

[0032] According to some embodiments of the present disclosure, the first stage oxidation aging treatment includes adding the oxidant to convert 20% to 50% of the Fe in the third mixture into 2+ Oxidized to Fe 3+ The aging treatment time is 1 h to 6 h. The remaining multi-stage oxidation aging treatment includes adding the oxidant to 2+ Oxidized to Fe 3+ For example, in the oxidation aging treatment, Fe 2+ The total oxidation amount can be 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48% or 50%.

[0033] According to some embodiments of the present disclosure, the aging time of each oxidation aging treatment is 1 h to 6 h. For example, it can be 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h, 4 h, 4.2 h, 4.4 h, 4.6 h, 4.8 h, 5 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h or 6 h.

[0034] According to some embodiments of the present disclosure, the segmented oxidation aging treatment has two segments, including a first-stage oxidation aging treatment and a second-stage oxidation aging treatment; The first stage oxidation aging treatment includes adding the oxidant to convert 20% to 50% of the Fe 2+ Oxidized to Fe 3+, the aging time is 1 h~6 h; The second stage oxidation aging treatment includes continuing to add the oxidant to 2+ Oxidized to Fe 3+ The aging time is 1 h~6 h.

[0035] According to some embodiments of the present disclosure, the segmented oxidation aging treatment has three segments, including a first-stage oxidation aging treatment, a second-stage oxidation aging treatment, and a third-stage oxidation aging treatment; The first stage oxidation aging treatment includes adding the oxidant to convert 20% to 45% of the Fe 2+ Oxidized to Fe 3+ , the aging time is 1 h~6 h; The second stage oxidation aging treatment includes continuing to add the oxidant to convert 30% to 50% of Fe 2+ Oxidized to Fe 3+ , the aging time is 1 h~6 h; The three-stage oxidation aging treatment includes continuing to add the oxidant to 2+ Oxidized to Fe 3+ The aging time is 1 h~6 h.

[0036] According to some embodiments of the present disclosure, the total aging time in the staged oxidation aging treatment is 3 h to 18 h. For example, it can be 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h, 10 h, 10.5 h, 11 h, 11.5 h, 12 h, 12.5 h, 13 h, 13.5 h, 14 h, 14.5 h, 15 h, 15.5 h, 16 h, 16.5 h, 17 h, 17.5 h or 18 h.

[0037] According to some embodiments of the present disclosure, the calcination temperature is 580°C to 750°C.

[0038] According to some embodiments of the present disclosure, the calcination temperature is 590°C to 740°C. For example, it may be 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C or 740°C.

[0039] According to some embodiments of the present disclosure, the calcination time is 2 h to 4 h. For example, it can be 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h or 4 h.

[0040] According to some embodiments of the present disclosure, step 2) further includes a pre-calcination treatment, which includes at least one of washing and drying.

[0041] According to some embodiments of the present disclosure, the first solid-liquid separation, the second solid-liquid separation, and the third solid-liquid separation each independently include at least one of filtration, centrifugation, suction filtration, and filter pressing.

[0042] The application of the above method according to the second aspect of the present disclosure in the recovery of iron phosphate dust collection material.

[0043] Other features and advantages of the present disclosure will be set forth in the following description, and in part will be apparent from the description, or may be learned by practicing the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 A flow chart of a method for preparing iron phosphate for a battery; Figure 2 This is the XRD spectrum of the iron phosphate dust collecting material; Figure 3 is the XRD spectrum of anhydrous ferric phosphate prepared in Example 1; Figure 4A This is a SEM image of the anhydrous ferric phosphate prepared in Example 1 (the scale bar is 4 microns); Figure 4B This is a SEM image of the anhydrous ferric phosphate prepared in Example 1 (the scale bar is 40 microns); Figure 5 is a SEM image of ferric phosphate dihydrate prepared in Comparative Example 2 (the scale bar is 4 microns); Figure 6 This is a particle size distribution diagram of the anhydrous ferric phosphate prepared in Example 1; Figure 7 This is a cross-sectional SEM image of the anhydrous ferric phosphate prepared in Example 1; Figure 8 The anhydrous ferric phosphate obtained in Example 1 and Comparative Example 2 under the same sand milling conditions D 50 -t change graph. DETAILED DESCRIPTION

[0045] The concept of the present disclosure and the technical effects produced will be clearly and completely described below in conjunction with embodiments to fully understand the purpose, features and effects of the present disclosure.

[0046] The reagents used without indicating the manufacturer are all conventional products that can be purchased from the market.

[0047] In the description of the present disclosure, the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, or product comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, or products.

[0048] When a numerical range is disclosed in the present disclosure, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in the present disclosure should be understood to include any and all subranges included therein.

[0049] The term "not higher than" means less than or equal to, and should be understood to include the number itself.

[0050] The term "not less than" means greater than or equal to, and should be understood to include the number itself.

[0051] Unless otherwise specified, the terms “about” or “approximately” in the present disclosure indicate that an error within ±5% is allowed.

[0052] In the embodiments of the present disclosure, the iron phosphate dust collecting material used is sourced from Hunan Bangpu Recycling Technology Co., Ltd.; in terms of mass percentage, the H2O content in the iron phosphate dust collecting material is 3.2%, the Fe content is 35.3%, the P content is 20.1%, and the contents of other impurity elements (such as Ca, Mg, Na, etc.) are all less than 10 ppm.

[0053] The content of trace elements in the following solutions, iron phosphate dust collection materials, and anhydrous iron phosphate was tested using ICP inductively coupled plasma atomic emission spectrometry (ICP-AES) equipment. The precipitate needs to be completely dissolved in an acidic solution before measurement, and the iron content in the solution is tested by potassium dichromate titration. The phosphorus content in the iron phosphate precipitate is tested using the quinoline molybdate gravimetric method, and the molar ratio of Fe to P is calculated.

[0054] Example 1 This example provides a method for preparing iron phosphate for battery, the steps are as follows: (1) Leaching: The iron phosphate dust collecting material was mixed with a 50% phosphoric acid aqueous solution at a material-liquid ratio of 50 g:1 L for leaching, the leaching temperature was 50°C, the leaching time was 2 h, and the dissolution rate was greater than 99%; solid-liquid separation was performed, and excess iron powder was added to the liquid phase (the molar amount of the iron powder was about 1.15 times that of the P element in the phosphoric acid aqueous solution, and the mass ratio of the iron phosphate dust collecting material to the iron powder was 0.09:1), and the reaction was carried out at 60°C for 6 h, and filtered to obtain a leachate; the leachate was diluted to a Fe concentration of about 110 g / L to obtain a reaction solution.

[0055] (2) Iron phosphate precipitation crystallization: In the multi-stage oxidation aging treatment (multi-stage precipitation), the hydrogen peroxide and Fe 2+ Hydrogen peroxide is added in excess of 10% to 20% to ensure the efficiency of the oxidation reaction. In the first stage oxidation aging treatment, the second stage oxidation aging treatment, and the third stage oxidation aging treatment, the Fe content in the reactants is confirmed by potassium dichromate titration before aging treatment. 2+ Total oxidation amount.

[0056] (2-1) The reaction solution was added to a reaction vessel, heated to 90° C., and then a surface dispersant SDS was added to obtain a mixed solution.

[0057] Among them, the mass ratio of SDS to iron in the reaction solution is 0.001495:1.

[0058] (2-2) One-stage oxidation aging treatment: At 90°C, 30% hydrogen peroxide was added to the mixed solution to control Fe 2+ The total oxidation amount was 20%, and the aging was carried out for 3 h.

[0059] (2-3) Second stage oxidation aging treatment: At 90°C, continue to add 30% hydrogen peroxide to control Fe 2+ The total oxidation amount was 70%, and the aging was carried out for 3 h.

[0060] (2-4) Three-stage oxidation aging treatment: At 90°C, 30% hydrogen peroxide was added to control Fe 2+ The total oxidation amount is 100%, and the temperature is kept for 3 hours. After the reaction is completed, the product is filtered to separate the dihydrated iron phosphate and the filtrate. The filtrate can be used to dilute the concentrated phosphoric acid and the leaching solution.

[0061] (2-5) Sintering: After secondary countercurrent washing and drying of the dihydrated ferric phosphate, the ferric phosphate was calcined at 600 °C for 2 h to obtain anhydrous ferric phosphate.

[0062] Example 2 This example provides a method for preparing iron phosphate for battery, the steps are as follows: (1) Leaching: The iron phosphate dust collecting material was mixed with a 50% phosphoric acid aqueous solution at a material-liquid ratio of 50 g:1 L for leaching, the leaching temperature was 40°C, the leaching time was 2 h, and the dissolution rate was greater than 99%; solid-liquid separation was performed, and excess iron powder was added to the liquid phase (the molar amount of the iron powder was about 1.05 times that of the P element in the phosphoric acid aqueous solution, and the mass ratio of the iron phosphate dust collecting material to the iron powder was 0.25:1), and the reaction was carried out at 60°C for 8 h, and filtered to obtain a leachate; the leachate was diluted to a Fe concentration of about 160 g / L to obtain a reaction solution.

[0063] (2) Iron phosphate precipitation crystallization: In the multi-stage oxidation aging treatment, hydrogen peroxide and Fe 2+ Hydrogen peroxide is added in excess of 10% to 20% to ensure the efficiency of the oxidation reaction. In the first stage oxidation aging treatment, the second stage oxidation aging treatment, and the third stage oxidation aging treatment, the Fe content in the reactants is confirmed by potassium dichromate titration before aging treatment. 2+ Total oxidation amount.

[0064] (2-1) The reaction solution was added to a reaction kettle, heated to 90° C., and then a surface dispersant SDBS was added to obtain a mixed solution.

[0065] The mass ratio of SDBS to the iron element in the reaction solution is 0.00299:1.

[0066] (2-2) One-stage oxidation aging treatment: At 90°C, 30% hydrogen peroxide was added to the mixed solution to control Fe 2+ The total oxidation amount was 20%, and the aging was carried out for 3 h.

[0067] (2-3) Second stage oxidation aging treatment: At 90°C, continue to add 30% hydrogen peroxide to control Fe 2+ The total oxidation amount was 60%, and the aging was carried out for 2 h.

[0068] (2-4) Three-stage oxidation aging treatment: At 90°C, 30% hydrogen peroxide was added to control Fe 2+ The total oxidation amount is 100%, and the product is kept warm for 2 h. After the reaction is completed, the product is filtered to separate the dihydrated iron phosphate and the filtrate. The filtrate can be used to dilute the concentrated phosphoric acid and the leaching solution.

[0069] (2-5) Sintering: After secondary countercurrent washing and drying of the dihydrated ferric phosphate, the ferric phosphate was calcined at 600 °C for 2 h to obtain anhydrous ferric phosphate.

[0070] Example 3 This example provides a method for preparing iron phosphate for battery, the steps are as follows: (1) Leaching: The iron phosphate dust collecting material was mixed with a 50% phosphoric acid aqueous solution at a material-liquid ratio of 50 g:1 L for leaching, the leaching temperature was 40°C, the leaching time was 4 h, and the dissolution rate was greater than 99%; solid-liquid separation was performed, and excess iron powder was added to the liquid phase (the molar amount of the iron powder was about 1.10 times that of the P element in the phosphoric acid aqueous solution, and the mass ratio of the iron phosphate dust collecting material to the iron powder was 0.45:1), and the reaction was carried out at 60°C for 8 h, and filtered to obtain a leachate; the leachate was diluted to a Fe concentration of about 160 g / L to obtain a reaction solution.

[0071] (2) Iron phosphate precipitation crystallization: In the multi-stage oxidation aging treatment, hydrogen peroxide and Fe 2+ Hydrogen peroxide is added at an excess of 10% to 20% to ensure the efficiency of the oxidation reaction. In the first-stage oxidation aging treatment and the second-stage oxidation aging treatment, the Fe content in the reactants is confirmed by potassium dichromate titration before aging treatment. 2+ Total oxidation amount.

[0072] (2-1) The reaction solution was added to a reaction kettle, heated to 90° C., and then a surface dispersant PPEA-15 (polyether surface dispersant, provided by Shanghai Sunray Polymer Materials Co., Ltd.) was added to obtain a mixed solution.

[0073] Among them, the mass ratio of PPEA-15 to iron in the reaction solution is 0.00299:1.

[0074] (2-2) One-stage oxidation aging treatment: At 90°C, 30% hydrogen peroxide was added to the mixed solution to control Fe 2+ The total oxidation amount was 20%, and the aging was carried out for 3 h.

[0075] (2-3) Second stage oxidation aging treatment: At 90°C, continue to add 30% hydrogen peroxide to control Fe 2+ The total oxidation amount is 100%, and the temperature is kept for 6 hours. After the reaction is completed, the product is filtered to separate the dihydrated iron phosphate and the filtrate. The filtrate can be used to dilute the concentrated phosphoric acid and the leaching solution.

[0076] (2-4) Sintering: After secondary countercurrent washing and drying of the dihydrated ferric phosphate, the ferric phosphate was calcined at 600 °C for 2 h to obtain anhydrous ferric phosphate.

[0077] Example 4 This example provides a method for preparing iron phosphate for battery, the steps are basically the same as those in Example 1, the only difference being that in step (1), "diluting the leachate to a Fe concentration of about 110 g / L" is replaced by "diluting the leachate to a Fe concentration of about 200 g / L".

[0078] Example 5 This example provides a method for preparing iron phosphate for battery, and the steps are basically the same as those in Example 1, with the only difference being that the heating temperature in step (2-1) is replaced from 90°C to 85°C.

[0079] Example 6 This example provides a method for preparing iron phosphate for battery, and the steps are basically the same as those in Example 1, with the only difference being that in step (2-1), the mass ratio of SDS to the iron element in the reaction solution is 0.004485:1.

[0080] Example 7 This example provides a method for preparing iron phosphate for batteries, and the steps are basically the same as those in Example 1, with the only difference being that in step (2-1), the surface dispersant SDS is replaced with SRC-JX-1 (a surfactant containing quaternary ammonium groups and hydroxyl groups, provided by Shanghai Sanrui Polymer Materials Co., Ltd.), and the mass ratio of SRC-JX-1 to the iron element in the reaction solution is 0.004485:1.

[0081] Example 8 This example provides a method for preparing iron phosphate for batteries. The steps are basically the same as those in Example 1, with the only difference being that in step (2-1), the surface dispersant SDS is replaced with SRC-JX-2 (a hydroxyl-containing nonionic surfactant provided by Shanghai Sanrui Polymer Materials Co., Ltd.), and the mass ratio of SRC-JX-2 to the iron element in the reaction solution is 0.004485:1.

[0082] Example 9 This example provides a method for preparing iron phosphate for batteries, and the steps are basically the same as those in Example 1, with the only difference being that in step (2-1), the surface dispersant SDS is replaced with SRC-JX-3 (a surfactant containing quaternary ammonium groups and hydroxyl groups, provided by Shanghai Sanrui Polymer Materials Co., Ltd.), and the mass ratio of SRC-JX-3 to the iron element in the reaction solution is 0.004485:1.

[0083] Example 10 This example provides a method for preparing iron phosphate for battery, the steps are basically the same as those in Example 1, the only difference is that in step (2-2), the heat preservation aging time of an oxidation aging treatment is replaced by 2 h instead of 3 h.

[0084] Embodiment 11 This example provides a method for preparing iron phosphate for battery, and the steps are basically the same as those in Example 1, with the only difference being that the calcination temperature in step (2-5) is replaced from 600°C to 700°C.

[0085] Comparative Example 1 This example provides a method for preparing iron phosphate for battery, the steps are basically the same as those in Example 1, the only difference is that in step (1), the temperature of the mixed leaching of phosphoric acid aqueous solution and iron phosphate dust collection material is replaced by 80°C from 50°C.

[0086] Comparative Example 2 This example provides a method for preparing iron phosphate for battery, and the steps are basically the same as those in Example 1, with the only difference being that in step (2-1), a surface dispersant is missing.

[0087] Comparative Example 3 This example provides a method for preparing iron phosphate for batteries, and the steps are basically the same as those in Example 1, with the only difference being that: in step (2-1), a surface dispersant is missing; in step (2-3), SDS is added before a second-stage oxidation, wherein the mass ratio of SDS to the iron element in the reaction solution is 0.001495:1.

[0088] Comparative Example 4 This example provides a method for preparing iron phosphate for battery. The steps are basically the same as those in Example 1, except that the surface dispersant in step (2-1) is replaced by PEG3000 instead of SDS.

[0089] Comparative Example 5 This example provides a method for preparing iron phosphate for battery, and the steps are basically the same as those in Example 1, with the only difference being that the surface dispersant in step (2-1) is replaced by citric acid (CA, provided by Sinopharm Chemical Reagent Co., Ltd.) instead of SDS.

[0090] Comparative Example 6 This example provides a method for preparing iron phosphate for battery. The steps are basically the same as those in Example 1, except that steps (2-2) to (2-4) are replaced by "adding 30% hydrogen peroxide to the mixed solution to control the Fe 2+ The oxidation is complete; after the reaction is completed, filter press is performed to separate the dihydrated iron phosphate and the filtrate.

[0091] Comparative Example 7 This example provides a method for preparing iron phosphate for battery, and the steps are basically the same as those in Example 1, with the only difference being that in step (2-1), the mass ratio of SDS to the iron element in the reaction solution is 0.000897:1.

[0092] Comparative Example 8 This example provides a method for preparing iron phosphate for battery, and the steps are basically the same as those in Example 1, except that in step (2-1), the mass ratio of SDS to the iron element in the reaction solution is 0.00897:1.

[0093] Comparative Example 9 This example provides a method for preparing iron phosphate for battery, the steps are basically the same as those in Example 1, the only difference is that the calcination time in step (2-5) is replaced by 1 h from 2 h.

[0094] Comparative Example 10 This example provides a method for preparing iron phosphate for battery, the steps are basically the same as those in Example 1, the only difference is that the calcination temperature in step (2-5) is replaced from 600°C to 500°C.

[0095] Test example 1. Detect the content of iron, phosphorus and other impurity elements in the anhydrous ferric phosphate obtained in Examples 1 to 11 and Comparative Examples 1 to 10, and compare them with the industry standards to determine whether the products are qualified. X-ray diffraction (XRD), Malvern 3000 laser particle size analyzer, scanning electron microscope (SEM) and the like are used to characterize the composition, morphology and particle size of the anhydrous ferric phosphate.

[0096] The results are shown in Table 1. Figures 2 to 7 shown.

[0097] Table 1

[0098] The iron phosphate obtained in Examples 1 to 11 meets the requirements of "HG / T4701-2021 Iron Phosphate for Batteries" for anhydrous iron phosphate. The specific surface areas of the iron phosphates obtained in Comparative Examples 1 to 7 are all less than 3, which does not meet the requirements, and the iron phosphate particles show block precipitation. The anhydrous iron phosphate obtained in Comparative Example 8 has too small particle size, is easy to agglomerate, and is difficult to filter. The XRD phase of the iron phosphate obtained in Comparative Examples 9 to 10 has mixed peaks, which does not meet the requirements.

[0099] The methods of Examples 1 to 11 add a surface dispersant before the staged oxidation and aging treatment, thereby avoiding the formation of blocky crystal seeds in the early stage of crystallization. Combined with the subsequent multi-stage oxidation and aging treatment, the product BET and porosity are improved, and anhydrous iron phosphate with high BET and easy sanding is obtained. The method of Comparative Example 1 dissolves the iron phosphate dust collecting material with an aqueous phosphoric acid solution at a higher temperature, resulting in the direct spontaneous formation of blocky crystal nuclei, and subsequent precipitation and crystallization are all carried out on this basis, so qualified anhydrous iron phosphate cannot be obtained; if the blocky crystal nuclei are filtered out and then subjected to subsequent treatment, the purpose of recovery cannot be achieved. The method of Comparative Example 2 lacks a surface dispersant, and high-temperature oxidation is easy to directly produce blocky crystal nuclei, resulting in the subsequent multi-stage oxidation and aging treatment being difficult to achieve the corresponding effect. The method of Comparative Example 3 adds a surface dispersant after a stage of oxidation, at which time the crystal nuclei have been formed, and the purpose of controlling crystallization cannot be achieved. The surface dispersant PEG3000 used in the method of Comparative Example 4 has too large a viscosity after dissolution, and the dispersion effect is poor. The surface dispersant CA used in the method of Comparative Example 5 does not participate in complexation, adsorption and other reactions between particles, and cannot achieve a dispersion effect. The method of comparative example 6 lacks multi-stage oxidation aging treatment, and the crystal nuclei will form and grow rapidly, resulting in a low BET of the product. The method of comparative example 7 adds too little surface dispersant, and the ratio between the particles is too small, resulting in some particles being unable to combine and failing to play the role they should. The method of comparative example 8 adds too much surface dispersant, and the particle size is too small. The surface dispersant is easy to self-bind, resulting in the combination between the particles, and finally causing the particles to agglomerate. The methods of comparative examples 9 and 10 are not sintered thoroughly, and XRD shows the presence of dihydrate iron phosphate phase.

[0100] 2. The anhydrous ferric phosphate prepared in Examples 1 to 11 and Comparative Examples 1 to 10 was batched and sanded to confirm its sanding performance; the number of sanding times was recorded during the sanding. The specific steps are as follows: 10 kg of anhydrous ferric phosphate was mixed with 2.52 kg of lithium carbonate, 0.6 kg of glucose, 0.1 kg of superconducting carbon black, and 0.6 kg of PEG1500, and 25.6 kg of water was added to obtain a slurry. The slurry was first coarsely ground (10 min / time) by a sand mill (Guangdong Huijing Intelligent Equipment Co., Ltd., horizontal sand mill KNB-S) under the same conditions to a particle size of D 50 The coarsely ground slurry was then finely ground by a sand mill under the same conditions (10 min / time) to a particle size of D 50 Less than 0.5 μm.

[0101] The results are shown in Table 2.

[0102] Table 2

[0103] The iron phosphates prepared in Examples 1 to 11 have good sand grinding performance, while the iron phosphates prepared in Comparative Examples 1 to 7 have poor sand grinding performance.

[0104] 3. The anhydrous ferric phosphate prepared in Example 1 and Comparative Example 2 were mixed with water at a mass ratio of 1:4 to obtain slurry A and slurry B. A sand mill (Guangdong Huijing Intelligent Equipment Co., Ltd., horizontal sand mill KNB-S) was used to sand grind slurry A and slurry B under the same sand grinding conditions (10 min / time) to a particle size of D. 50 Less than 0.5 μm.

[0105] The results are as follows Figure 8 shown.

[0106] In D 50 Under similar conditions, compared with Comparative Example 2, the anhydrous ferric phosphate prepared in Example 1 can obtain a product that meets the requirements in a shorter sand milling time. This shows that the formation of blocky crystal nuclei will affect the sand milling performance of anhydrous ferric phosphate.

Claims

1. A method for preparing iron phosphate for battery, characterized in that: The following steps are involved: 1) preparing a first mixture of iron phosphate dust collection material and phosphoric acid aqueous solution, leaching treatment, and first solid-liquid separation to obtain a first liquid phase; preparing a second mixture of the first liquid phase and elemental iron, reacting, and second solid-liquid separation to obtain a second liquid phase; The leaching temperature is not higher than 50°C; the molar ratio of phosphorus in the phosphoric acid aqueous solution to the elemental iron is 1:1.05-1.2; 2) preparing a third mixture of the second liquid phase and a surface dispersant, and subjecting the third mixture to a staged oxidation aging treatment; After the third solid-liquid separation, a solid phase is obtained; and the solid phase is roasted to obtain the iron phosphate; The surface dispersant includes at least one of a cationic surfactant, an anionic surfactant, and a nonionic surfactant; the cationic surfactant includes a quaternary ammonium surfactant; the anionic surfactant includes at least one of SDS and SDBS; the nonionic surfactant includes at least one of a polyether surfactant and a hydroxyl surfactant; The number of segments of the segmented oxidation aging treatment is N, and N is a positive integer not less than 2; The calcination temperature is not less than 580° C. and the calcination time is not less than 2 h.

2. The method according to claim 1, characterized in that The material-liquid ratio of the iron phosphate dust collecting material to the phosphoric acid aqueous solution is 20 g to 200 g: 1 L; and / or, the phosphoric acid concentration in the phosphoric acid aqueous solution is 30% to 50%; And / or, the mass ratio of the ferric phosphate dust collecting material to the elemental iron is 0.06~0.6:

1.

3. The method according to claim 1, characterized in that The leaching treatment time is no longer than 4 h.

4. The method according to claim 1, characterized in that: The quaternary ammonium surfactant includes at least one of SRC-JX-1 and SRC-JX-3; And / or, the polyether surfactant includes PPEA-15; And / or, the hydroxyl surfactant comprises SRC-JX-2.

5. The method according to claim 1, characterized in that The reaction temperature of the reaction in step 1) is 50°C to 90°C; And / or, the reaction time of the reaction in step 1) is 6 h to 10 h.

6. The method according to claim 1, characterized in that The mass ratio of the iron element in the third mixture to the surface dispersant is 1:0.0014-0.0045.

7. The method according to claim 1, characterized in that The staged oxidation aging treatment includes one stage oxidation aging treatment to N stage oxidation aging treatment; Each stage of the staged oxidation-aging treatment comprises: adding an oxidant and performing an aging treatment.

8. The method according to claim 7, characterized in that The oxidant includes at least one of hydrogen peroxide, oxygen, ozone and air; And / or, the temperature of the staged oxidation aging treatment is 50°C to 90°C; And / or, the aging time of each oxidation aging treatment is 1 h to 6 h.

9. The method according to claim 7 or 8, characterized in that: The first stage oxidation aging treatment includes adding the oxidant to convert 20% to 50% of the Fe 2+ Oxidized to Fe 3+ The aging treatment time is 1 h to 6 h; the remaining multi-stage oxidation aging treatment includes adding the oxidant to the remaining Fe 2+ Oxidized to Fe 3+ and performing the aging treatment.

10. Use of the method according to any one of claims 1 to 9 in the recovery of iron phosphate dust collection materials.

Citation Information

Patent Citations

  • Method for recovering iron phosphate from lithium iron phosphate extraction slag and application thereof

    CN115196609A

  • Method for preparing iron phosphate through continuous oxidation process

    CN116534824A

  • Method for preparing battery-grade iron phosphate

    CN117401659A

  • Method for recycling battery-grade iron phosphate and lithium salt from lithium iron phosphate waste and application of battery-grade iron phosphate and lithium salt

    CN118651832A

  • Lithium iron phosphate positive electrode material precursor as well as preparation method, device and application thereof

    CN118723955A